2023
DOI: 10.2196/47564
|View full text |Cite
|
Sign up to set email alerts
|

User Intentions to Use ChatGPT for Self-Diagnosis and Health-Related Purposes: Cross-sectional Survey Study

Abstract: Background With the rapid advancement of artificial intelligence (AI) technologies, AI-powered chatbots, such as Chat Generative Pretrained Transformer (ChatGPT), have emerged as potential tools for various applications, including health care. However, ChatGPT is not specifically designed for health care purposes, and its use for self-diagnosis raises concerns regarding its adoption’s potential risks and benefits. Users are increasingly inclined to use ChatGPT for self-diagnosis, necessitating a de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(67 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…So far in the CRAFT-MD framework, the doctor-AI agent was provided with physical exam details from the case vignettes after conversing with the patient-AI agent, mirroring a healthcare visit in which some in-person evaluation occurs. However, with increasing use of AI chatbots for informal self-diagnosis prior to doctor visits 21 , we investigated the impact of removing physical exam information from the framework across all formats (Figure 4a, 4b; see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…So far in the CRAFT-MD framework, the doctor-AI agent was provided with physical exam details from the case vignettes after conversing with the patient-AI agent, mirroring a healthcare visit in which some in-person evaluation occurs. However, with increasing use of AI chatbots for informal self-diagnosis prior to doctor visits 21 , we investigated the impact of removing physical exam information from the framework across all formats (Figure 4a, 4b; see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…This study shows that while ChatGPT displays a high level of accuracy and completeness in clinical treatments and recommendations for challenging DBP cases, it still lacks in regards to diagnostic accuracy. With a large proportion of the general patient population willing to use ChatGPT for self-diagnosis, 21 Large-language models (LLMs) must be verified through real-world testing. Professionals should provide the right data and algorithmic guidelines to develop these tools further.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 80% of Americans utilize the internet for health care information and a recent study demonstrated 78.4% of patients are willing to use ChatGPT for self-diagnosis. 7,8 With patients turning to the internet for health care information more than ever, and AI becoming a central pillar of the online landscape, the quality of material generated by ChatGPT and AI tools like it should be evaluated.…”
Section: Accepted Manuscriptmentioning
confidence: 99%